Uses of Rationalist Pedagogy in Modern School Nº 1 of São Paulo (1913-1919) - Leutprecht, Douglas Bahr; Dallabrida, Norberto (Historia y Memoria de la Educación, 2019)
This article analyzes the uses of rationalist pedagogy, elaborated by the anarchist educator Francisco Ferrer y Guardia and his collaborators in the Modern School of Barcelona at the beginning of the 20th century, by the Modern School Nº 1, located in the city of São Paulo (Brazil). In addition to its strong anarchist and anticlerical content, rationalist pedagogy was characterized by scientific positivism, defending ideas such as integral education, learning through the senses, coeducation of social and gender classes and childhood hygiene. The execution of Ferrer y Guardia in 1909 unleashed in Brazil, as well as in other parts of the world, a great interest in his pedagogical thinking. From this movement came the Modern School Nº 1, directed, for the most part, by the anarchist João Penteado. The present work aims to understand the process of appropriation of rationalist pedagogy in such an institution, using, for this purpose, school newspapers and written documents produced in the institution directed by Penteado. The aticle concludes that, despite the idea that the Modern School Nº 1 was a school totally removed from the hegemonic pedagogical thought of the period, those involved in the institution resorted to the cultural resources they had available. In this way, a hybrid pedagogical approach was built in the school, which appropriated both the rationalist pedagogy and the pedagogical model existing in graduate schools, which in Brazil was called school group.